2020
DOI: 10.1037/edu0000378
|View full text |Cite
|
Sign up to set email alerts
|

Leaving the pond—Choosing an ocean: Effects of student composition on STEM major choices at university.

Abstract: Self-concept in mathematics (MSC) and interest in mathematics are important predictors of whether a student will choose to major in a science, technology, engineering, or mathematics (STEM) field at university. Research on the big-fish-little-pond effect (BFLPE) has shown that both predictors are affected by the achievement composition of students in schools. That is, given the same individual ability, students in higher achieving schools exhibit lower MSC and interest in mathematics than students in lower ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 68 publications
(169 reference statements)
0
10
0
Order By: Relevance
“…Structural constraints, normative expectations and individual motivation are factors posited by sociologists and psychologists that point to the joint influences of agency and structure in the service of life goals. Structural constraints undoubtedly influence individual choices (Settersten and Gannon, 2005;Archer, 2014). College students likely have different levels of freedom to choose their courses depending on the policies of their schools, majors, and year of studying.…”
Section: Introductionmentioning
confidence: 99%
“…Structural constraints, normative expectations and individual motivation are factors posited by sociologists and psychologists that point to the joint influences of agency and structure in the service of life goals. Structural constraints undoubtedly influence individual choices (Settersten and Gannon, 2005;Archer, 2014). College students likely have different levels of freedom to choose their courses depending on the policies of their schools, majors, and year of studying.…”
Section: Introductionmentioning
confidence: 99%
“…Our study builds on von Keyserlingk et al’s (2020) work about long-term effects of the BFLPE on university major choices and extends their findings in several ways. First, we address a research gap they identified, and focus on the role of social and dimensional comparisons for university major choices simultaneously.…”
Section: Theoretical Backgroundmentioning
confidence: 78%
“…Trautwein et al (2005) showed with a longitudinal German sample that the BFLPE predicted course choices in high school: Students with equal math achievement levels were less likely to choose advanced math courses in high schools with a higher mean math achievement. The results of another study (von Keyserlingk et al, 2020) showed that the association between the BFLPE and university major choice was quite small and mediated by its effect on students’ high school ability self-concepts. Studies focusing on dimensional comparison processes have shown that academic achievement, ability self-concepts, and STV positively predicted university major choice in the corresponding domain (i.e., math achievement and beliefs predicted a greater likelihood of selecting a STEM major), but negatively predicted enrollment in majors in noncorresponding domains (Gaspard et al, 2019; Jansen et al, 2021; Parker et al, 2012).…”
Section: Theoretical Backgroundmentioning
confidence: 95%
“…To address the issue of the pressure teachers feel in preparing students for exams, potential remedies include stress management interventions, such as cognitive-behavioral-based and mindfulness-based interventions (von Keyserlingk et al, 2020). Cognitive-behavioral-based interventions involve cognitive training and the practice of strategic behaviors, equipping teachers with both knowledge and skills to effectively manage workrelated stress (von Keyserlingk et al, 2020). On the other hand, mindfulness-based interventions emphasize cognitive and behavioral strategies that focus on the experience of feelings and thoughts, rather than the specific content of those thoughts.…”
Section: Discussionmentioning
confidence: 99%